Could REF-BY Improve Caring and Emotion Regulation on Nurses at Psychiatric Rehabilitation Center? - Rizki, Binta Mu'tiya; Andromeda, Andromeda; Swaraswati, Yogi; Sukoasih, Yuni Dwi (Insight: Jurnal Ilmiah Psikologi, 2022)
Carrying out duties as a nurse for patients with mental illness causes work stress that could affect caring abilities. Good-quality caring is very necessary to support patientsâ€™ recovery. The phenomenon of nurses with low-quality caring can be caused by a lack of ability to regulate emotions. The purpose of this study is to test the effectiveness of REF-BY training to improve caring by controlling work stress and neuroticism personality variables. The method used in this study is an experiment employing a one group pretest-posttest design and the Mann Whitney U test as data analysis technique. This study involved 6 nurses working in one psychiatric Â rehabilitation center. The results of the data analysis showed that based on the pretest and posttest and follow-up scores, REF-BY training could help improve caring skills significantly.